The Announcement of Sharia Bank’s Conditional Merger Agreement. How Investor Reacted? : Event Study at BRI Syariah - Syamsuddin Syamsuddin; Versiandika Yudha Pratama (Profesional Muda Cendekia Publishing, 2021)
This study aims to determine there is a difference in average abnormal return of BRI Syariah before and after the signing of the Conditional Merger Agreement (CMA), which is on October 12th, 2020. This research used event study for method and the data in this study are secondary data in the form of stock price data of BRI Syariah. The event window in this study for 11 (eleven) working days which is 5 (five) days before the event, 1 (one) day when the event occurs and 5 (five) days after the signing of the Conditional Merger Agreement (CMA) BUMN sharia bank. Meanwhile, the estimated period is set for 120 exchange days, namely at t-125 to t-6. Test conducted by paired sample t-test. The results of the paired sample t-test showed that there is no significant difference between the average abnormal return of BRI Syariah shares before and after the signing of the Conditional Merger Agreement. It can be concluded that neither the market nor investors reacted to the signing of the Conditional Merger Agreement (CMA) that occurred at BRI Syariah Bank.